Respostas
respondido por:
2
(x - 5)² = 4
O quadrado da diferença de dois termos
x² -2x . 5 + (-5)² = 4
x² - 10x + 25 = 4
x² - 10x + 25 - 4 = 0
x² - 10x + 21 = 0
Por fatoração:
(x - 7) . (x - 3)
x - 7 = 0
x' = 7
x -3 = 0
x'' = 3
S = {7, 3}
O quadrado da diferença de dois termos
x² -2x . 5 + (-5)² = 4
x² - 10x + 25 = 4
x² - 10x + 25 - 4 = 0
x² - 10x + 21 = 0
Por fatoração:
(x - 7) . (x - 3)
x - 7 = 0
x' = 7
x -3 = 0
x'' = 3
S = {7, 3}
Helvio:
Obrigado Tiago
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás